Combined use of 3D-printed customized prostheses and denosumab for the treatment of giant cell tumor of the distal radius: clinical outcomes and efficacy - Li, Ye; Li, Longqing; He, Xuanhong; Gong, Taojun; Li, Zhuangzhuang; Liu, Xiaoyan; Luo, Yi; Zhou, Yong; Min, Li; Tu, Chongqi (Frontiers in Oncology, 2025)
ObjectiveTo investigate the short- and mid-term clinical efficacy of denosumab combined with 3D-printed prosthesis in the treatment of patients with giant cell tumor of the distal radius.MethodsFrom January 2016 to January 2022, 20 patients with giant cell tumor of the distal radius underwent denosumab treatment combined with 3D-printed prosthetic reconstruction at our hospital. This study evaluates the short- and mid-term efficacy by analyzing clinical cases where denosumab was used preoperatively, followed by 3D-printed biological prosthesis reconstruction of the distal radius tumor segment defect. We analyzed complications, function, survival rate, and recurrence rate after denosumab treatment and surgery.ResultsA total of 20 patients underwent 3D-printed biological prosthesis replacement of the distal radius, with an average of 5.5 doses (range, 4-7) of 120 mg denosumab administered preoperatively. The average age of the patients was 37.2 years (range, 17–52 years), with an average follow-up of 47.3 months (range, 24–72 months). At the last follow-up, no local recurrence or pulmonary metastasis was observed in any of the patients. The pre-treatment wrist range of motion (ROM) was: extension 17.0° (range, 5°-25°), flexion 17.3° (range, 10°-30°), pronation 19.3° (range, 10°-30°), and supination 18.8° (range, 10°-30°). After denosumab treatment and before prosthesis replacement, wrist ROM improved to: extension 33.0° (range, 15°-70°), flexion 39.0° (range, 15°-60°), pronation 37.5° (range, 20°-55°), and supination 40.5° (range, 20°-60°). After prosthesis replacement, wrist ROM further improved to: extension 46.4° (range, 20°-80°), flexion 55.8° (range, 20°-85°), pronation 57.0° (range, 30°-80°), and supination 61.8° (range, 25°-80°). The average Mayo wrist score was 71.8 points, and the average Disabilities of the Arm, Shoulder and Hand (DASH) score was 16.2 points. Regarding complications, one patient experienced wrist subluxation postoperatively, and two patients experienced distal radioulnar joint separation.ConclusionDenosumab treatment during the prosthesis production period improved wrist function and inhibited tumor progression. Patients undergoing 3D-printed biological prosthesis replacement of the distal radius showed good short- and mid-term functional outcomes, with good integration of the prosthesis with the host bone and low prosthesis-related complications. The overall clinical outcomes were satisfactory, though long-term effects of the prosthesis require further observation.